Croatian resources for NooJ - Bekavac, Božo; Vučković, Kristina, Tadić, Marko (2007)
The work describes existing Croatian language resources, their conversion into NooJ and explains methodology for compund extraction from Wikipedia.
Projekt MZOS
ENG